2017
DOI: 10.1007/s12471-017-1039-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation in patients who underwent primary percutaneous coronary intervention for acute myocardial infarction: determinants of programme participation and completion

Abstract: BackgroundHospital length of stay after acute myocardial infarction (AMI) treated with primary percutaneous coronary intervention (pPCI) has reduced, resulting in more limited patient education during admission. Therefore, systematic participation in cardiac rehabilitation (CR) has become more essential. We aimed to identify patient-related factors that are associated with participation in and completion of a CR programme.MethodsWe identified 3,871 consecutive AMI patients who underwent pPCI between 2003 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
4
34
2
4
Order By: Relevance
“…Similar to prior studies, diabetes proved again to be a negative factor when it comes to functional benefit from CR . This may stem from the fact that patients with diabetes are less likely to be enrolled in CR, and less likely to be adherent . Another possible explanation is lower baseline fitness.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar to prior studies, diabetes proved again to be a negative factor when it comes to functional benefit from CR . This may stem from the fact that patients with diabetes are less likely to be enrolled in CR, and less likely to be adherent . Another possible explanation is lower baseline fitness.…”
Section: Discussionsupporting
confidence: 68%
“…There was also no difference when it came to gender, since both male and female patients appeared to benefit in our study. Although that is an encouraging finding, women were still under‐represented in our study (29%), which is more of a reflection of poor enrollment of women in our and other CR programs across the country …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Specifically in women, where the benefits are consistently the same as in men they remain of low representative in most studies, with only 15% to 25%, presenting themselves with more risk factors and probably more severe CHD 9,24,29,30 One study found that the probability of women engaging in CR program was 7.1% lower than men. 24 In a study with 3,871 patient, where 1,497 39%) engaged CR program and 1,193 completed it, the chance of completing CR program after primary PCI for acute MI was evaluated.…”
Section: Participation In Cr Programsmentioning
confidence: 99%
“…24 In a study with 3,871 patient, where 1,497 39%) engaged CR program and 1,193 completed it, the chance of completing CR program after primary PCI for acute MI was evaluated. Sunamura et al 29 found that elderly, female and low socioeconomic status patients were at increased risk of non-participation and non-completion of CR. They also found that patients with diabetes, current smokers and with history of prior MI were at risk of not completing the program.…”
Section: Participation In Cr Programsmentioning
confidence: 99%